HUBUNGAN LUAS LAHAN DENGAN FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI KEPUTUSAN PETANI MENGUSAHAKAN TANAMAN KARET DI KAMPUNG PEPAS EHENG KECAMATAN BARONG TONGKOK - Rita Mariati (UIR Press, 2013)
The purpose of this study was to determine the relationship between several factors; marketing, inheritance professions, level of education, and production on land holding of rubber farmers. This study was conducted in the village of pepas Eheng Barong Tongkok District from October to December 2012. A total of 38 sample farmers was selected using simple random sampling method. The data were collected through personal interview and field observations. The data were analysed using a descriptive statistical analysis in the form of frequency tables, percentages, mean, and total mean scores and Chi-square tests, and Pearson’s contingency correlation test. The results show that the four factors influenced farmers' decisions to cultivate rubber farm in Kampung Pepas Eheng mainly X2 = 66.11 > X2 = 9.49. Pearson contingency coefficient value was 0.078. It indicates that the relationship among variables towrd land holding was very weak